Pengaruh Halal Knowledge, Islamic Religiosity dan Kualitas Produk terhadap Keputusan Pembelian Produk Wardah - Achmad, Dewi Nabila; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2021)
Kosmetik the main needs of society in countries that are predominantly Muslim, Wardah is a brand of cosmetics brand in the first country to include halal label on its products, and is also known by some communities in Indonesia as products that demonstrate its existence, safe, high quality and also halal. This study aims to determine the effect of halal knowledge, religiosity and product quality on purchasing decisions of wardah cosmetics on Muslim consumers in Surabaya. The sampling technique used is a non-probability sampling technique in the form of purposive sampling with the population being Muslim consumers in the city of Surabaya, East Java. This study uses quantitative research methods from primary data. Meanwhile, the research sample amounted to 100 respondents. Hypothesis testing using multiple linear regression analysis on SPSS version 24. Based on the results of this study Partially, in this study, the variables of halal knowledge and Islamic religiosity did not have a significant effect on purchasing decisions. While partially in this study product quality variables have a significant effect on purchasing decisions. And simultaneously the three independent variables halal knowledge, Islamic religiosity and product quality affect the dependent variable, namely purchasing decisions..